Ἀντιστάσεις μνήμης – Μαρτυρίες Ἀρχείου: Ἡ περίπτωση ἑνὸς ἀθηναϊκοῦ σπιτιοῦ τῆς ὀθωνικῆς περιόδου (Κυδαθηναίων 11-13) - Φατσέα Ρένα (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2015)
This article focuses on the case of an extant Athenian house of the early Othonian period, which is located in the easternmost section of the old city of Athens (i.e., Plaka). It is a thorough study of the building’s architectural structure and its historical phasing along with the history of its inhabitation. It draws its documentation on the physical structure as such in association with a wealth of archival materials. A series of contracts related to the site and the building construction – i.e., a fortuitous discovery – constitute a rare piece of evidence contributing to the building’s history, its attribution (i.e., to Austrian architect Fr. Stauffert), original ownership (i.e., by French consul A. de Roujoux), and dating (i.e., in 1837-38 and construction in 3 phases). Along with the building as such, the paper seeks to both trace and document the history of its neighborhood (Alikokkou) and its physical transformations during the early decades of the modern state. To that purpose it builds primarily on the series of historical maps (which is the main focus of the volume that contains it), and secondarily on textual/ archival materials, that is, mainly building and property related contracts. Through the research a number of long-standing erroneous assumptions about the building are unveiled and corrected, such as its dating from the late Ottoman period, i.e., a long-standing misconception supported by its kinship to pre-modern house typologies featuring a hayat, that is, a second floor walled loggia giving on to a courtyard. Collective memory’s inertia preserved this hypothesis turning it gradually into historical factuality. This paper attempts to recover this and other gaps in the building’s history and hence reconstruct its history proper. In that sense, it also serves as a critical commentary on how easily collective memory often slips into the status of factual history, especially when it lacks the data, or depends heavily upon orally transmitted information as is the case with vernacular (i.e., anonymous) architecture.